The Effect of Family Planning Services and the Human Development Index on Long-Term Contraceptive Method Use and Fertility in Indonesia: Pengaruh Layanan Keluarga Berencana Dan Indeks Pembangunan Manusia Pada Penggunaan Metode Kontrasepsi Jangka Panjang Dan Fertilitas Di Indonesia - Sari, Nurul Puspita; Munir, Ahmad; Ramli AT, M.; Iskandar, Madris (Universitas Negeri Surabaya, 2024)
The success of population control programs at the national level should be equitable across all provinces in Indonesia. However, differences in characteristics between regions and decentralization policies implemented by each local government have led to significant TFR disparities in each province in Indonesia. Long-acting contraceptives are considered effective as the main requirement to reduce the rate of population increase. The government has set targets to reduce the TFR and ensure equitable distribution of family planning programs throughout Indonesia. The equitable distribution of family planning programs will have an impact on reducing the birth rate. This study aims to see how contextual factors can reduce fertility through the use of contraceptive methods in Indonesia. The result of this study is that the percentage of women who use long-acting contraceptive methods has the largest effect on reducing TFR at -0.562, while the number of family planning villages and HDI have an effect of -0.12 and -0.36 on reducing TFR in Indonesia.